The complete mitochondrial genome of Blattisocius keegani Fox (Acari: Mesostigmata) and the related phylogenetic analyses. Issue 1 (17th February 2019) - Wu, Lingzhi; Cheng, Shiyu; Guo, Liuling; Mo, Weifen; Xia, Bin; Zou, Zhiwen
ABSTRACT: Blattisocius Keegan is a genus of predatory mites in the family Blattisociidae, with potential utility as biological control agents. In the present study, Illumina HiSeq was used to sequence the complete mt genome of B. keegani Fox. The mt genome of B. keegani was a circular DNA molecule of 17, 314 bp. With a 1, 935 bp-long non-coding region, it is the second largest mt genome in Acari. All 37 genes expected to be present in a standard metazoan mitogenome were identified in this genome. Phylogenetic analyses of 28 additional species of Acari were then performed based on the mt genome. Bayesian inference (BI) and Maximum likelihood (ML) algorithm were used to analyse the sequence data. Compared with Limulus polyphemus, rearrangements of 34 genes and changes of three genes orientation (trnE, trnF and trnS1 ) in B. keegani were observed. Additionally, the gene order of the six mesostigmata mites used in the study showed a lack of conserved gene blocks. BI and ML trees based on 13 protein-coding genes suggested that B. keegani was clustered with E. nicholsi and P. persimilis into a Phytoseioidea branch, which was consistent with the traditional classifications result.